SISTEM PENDUKUNG KEPUTUSAN PENJURUSAN SMA NEGERI 1 KEDUNGADEM MENGGUNAKAN METODE AHP (Analitychal Hierarchy Process) - Meilia , Venny; Irsyada , Rahmat (Multidisciplinary Applications of Quantum Information Science (Al-Mantiq), 2024)
This research was developed for a Major Decision Support System Using the AHP (Analythy Hierarchy Process) Method at SMA Negeri 1 Kedungadem. In the Indonesian Education curriculum, the selection of majors at the SMA level is an important stage that requires careful assessment of the Criteria. The AHP method is used to assist students in transmitting criteria such as Mathematics, Science, Social Sciences, English, and Indonesian in choosing the appropriate major.